Rapidly progressive respiratory failure due to antisynthetase syndrome related interstitial lung disease. Issue 5 (12th April 2023) - Almubarek, Marwan; Boy, Darryl P.; Lalla, Usha; Allwood, Brian W.; Irusen, Elvis M.; Koegelenberg, Coenraad F. N.
Abstract: A 65‐year‐old female was admitted with rapidly progressive respiratory failure requiring intubation and mechanical ventilation. She was considered to have an infective exacerbation of underlying interstitial lung disease (ILD). She improved on antibiotics, but the interstitial process progressed rapidly, and she could not be weaned. An antimyositis antibody panel yielded a strongly positive anti‐Jo‐1 and anti‐Ro 52. A diagnosis of antisynthetase syndrome (ASS) associated ILD, a very rare disease with high mortality, was made. She was managed with high‐dose corticosteroids and intravenous immunoglobulin therapy and was eventually liberated from mechanical ventilation. This case highlights the importance of considering ASS in an otherwise unexplained rapidly progressive ILD requiring mechanical ventilation. Abstract : Rapidly progressive respiratory failure due to antisynthetase syndrome related interstitial lung disease.